Assessment of soil characteristics in orchard - Nagy, A.; Fórián, T.; Tamás, J.; Szabó, Z.; Nyéki, J.; Soltész, M. (International Journal of Horticultural Science, 2012)
The research field was at Siófok, in Hungary, which is situated in the South East side of Lake Balaton. The physical characteristic of the soil is sandy loam and loam and the peach orchard is irrigated. The detailed goals were mapping and analyzing of physical properties of the soil in water management point of view, mapping the acidity and CaCO3content of soil for precision liming, measurement of humus the element content. Sites with different physical characteristics (from sandy loam to loamy clay) could be distinguished. The reason for this is that besides the possible increase of clayminerals, the increasing rate of colloidal humus content contributes to larger soil plasticity. Statistics also proved positive and strong correlation (r=0.822) between the soil plasticity and humus content. In the case of pH, only a small part of the orchard is has to be limed, since most of the orchard has neutral pH, which is advantageous for nuts and stone fruits. It has to be mentioned, that the CaCO3 supply is also appropriate for the stone fruits. Based on the results hyperspectral imagery can be a good solution for detecting calciferous soils, although these measurements are still need validation.